Socio-Economic Status and Current Business Situation of Cane Based Furniture Entrepreneurs in Bangladesh: An Empirical Study - Hasan, Md Kamrul; Neela, Nayeema Maswood (Journal of Business and Technology (Dhaka), 2016)
Cane based furniture business is one of the least researched areas in Bangladesh. The purpose of the present study is to appraise socio-economic conditions and business policy of cane based furniture in the study area of Sylhet city, Bangladesh. The study reveals that 57% of cane furniture enterprises is small, 36% is medium and 7% is large in size. The average investment, production and profit range around Tk. 2, 80,000, Tk. 2,21,916 and Tk. 22,500 respectively per enterprise. Sofa, chair and rocking chair are the most demanded and profitable items. The study also reveals that 51% of entrepreneurs are suffering from shortage of capital and raw materials, whereas 35% are suffering from unskilled labor and adequate transportation facilities. High price due to high cost, low demand, archaic and common design, less promotion are the major problems of cane furniture. The study suggests that entrepreneurs should create demand for cane furniture among all classes of people through proper promotional programs, newest design, adding new features, improving quality and making the product available to all over the country through proper distribution. Government should patronize this industry by giving financial and institutional supports. Journal of Business and Technology (Dhaka) Vol.10(1) 2015; 93-108